Quality of Life, Participation, and Functional Status in Cerebral Palsy: A 13-year Follow-up Study - Bilinc DOGRUOZ KARATEKIN; Afitap ICAGASIOGLU (Medeniyet Medical Journal)
Objective: This study aimed to investigate the current status and changes in motor and functional status, participation, and quality of life of individuals with cerebral palsy (CP) during the 13-year follow-up. Methods: Data from the database were retrospectively analyzed, including comorbidities, mobility status, orthotic usage, and information about the rehabilitation program and follow-up. The EuroQol 5-Dimension 3-Level (EQ-5D-3L) was used to measure the health-related quality of life. Results: Of our participants, 38.4% could independently walk 13-years ago, which increased to 51.2% presently. The orthotic usage decreased from 48.7% to 25.6%, and the rate of continuing rehabilitation decreased from 100% to 58.9%. The mean EQ-5D-3L score was 0.36+-0.42, and the mean EQ-visual analog scale score was 68+-24.01. Conclusions: Individuals with CP and their caregivers should be aware that CP is a lifelong disease and their continuity in rehabilitation programs should be encouraged. Independence in daily life activities should be aimed and participation in social life should be ensured.